2020
DOI: 10.1152/ajpheart.00235.2020
|View full text |Cite
|
Sign up to set email alerts
|

Acute mitochondrial antioxidant intake improves endothelial function, antioxidant enzyme activity, and exercise tolerance in patients with peripheral artery disease

Abstract: Peripheral artery disease (PAD) is a manifestation of atherosclerosis in the leg arteries, which causes claudication. This may be in part due to vascular mitochondrial dysfunction and excessive reactive oxygen species (ROS) production. A mitochondrial-targeted antioxidant (MitoQ) has been shown to improve vascular mitochondrial function which, in turn, led to improved vascular function in older adults and animal models. However, the roles of vascular mitochondria in vascular function including endothelial func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…Irreparable mitochondrial damage will release pro-apoptotic proteins into the cytoplasm and initiate the mitochondria-mediated death pathway. Endothelial mitochondrial dysfunction has been linked to several diseases such as diabetes-induced microvascular injury, cerebral ischemia-reperfusion injury (Zhang et al, 2020), nephropathy (Zhai et al, 2020), peripheral artery disease (Park et al, 2020), and pulmonary artery hypertension (Wang et al, 2020). Many researches have observed the role of mitochondrial damage in triggering endothelial dysfunction upon ox-LDL treatment (Li et al, 2018, Li et al, 2020Yuan et al, 2019;Xie et al, 2020), suggesting an urgent need for therapies that protect endothelial mitochondria in order to reduce atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%
“…Irreparable mitochondrial damage will release pro-apoptotic proteins into the cytoplasm and initiate the mitochondria-mediated death pathway. Endothelial mitochondrial dysfunction has been linked to several diseases such as diabetes-induced microvascular injury, cerebral ischemia-reperfusion injury (Zhang et al, 2020), nephropathy (Zhai et al, 2020), peripheral artery disease (Park et al, 2020), and pulmonary artery hypertension (Wang et al, 2020). Many researches have observed the role of mitochondrial damage in triggering endothelial dysfunction upon ox-LDL treatment (Li et al, 2018, Li et al, 2020Yuan et al, 2019;Xie et al, 2020), suggesting an urgent need for therapies that protect endothelial mitochondria in order to reduce atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%
“…There were additional benefits to hyperglycaemia and hepatic steatosis, as well as on multiple metabolically relevant lipid species. The usefulness of MitoQ treatment has not yet been investigated in patients with atherosclerosis, but it has recently been proven to significantly increase the endothelial function of aged persons and patients with peripheral artery disease [38,39], suggesting it has promising therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [146] reported that the acute oral intake of MitoQ (80 mg) improved maximal walking capacity and postponed the onset of limping in individuals with peripheral artery disease. The authors also observed increasing vascular endothelial function and SOD.…”
Section: Target Mitochondrial Antioxidants In Exercise-induced Oxidative Damagementioning
confidence: 99%